Métodos iterativos de análise hidráulica e dimensionamento ótimo por programação linear de redes de distribuição de água - Vieira, Ailton de Mesquita (1980)
A comparative evaluation of iteratives techniques of hydraulic analysis of water distribution networks according to Hardy Cross, Newton-Raphson and Linear Analysis methods, is introduced firstly. The best computational performance method, in case, the Newton-Raphson with a nodal formulation is used into an economical optimization of water distribution networks, which is only based on heuristic percepts. The outcomes of this heuristic optimization are compared to those obtained through an linear optimization model. This model uses linear programming together with a gradient search technique based on dual variables of the linear programming problem. The comparison of the results of the two methods is performed to evaluate the effectiveness of the linear optimization model in professional applications. The results obtained by this comparison indicate that satisfactory outcomes may be reached with the linear optimization model. However, computational limitations set constraints to the general use of the linear optimization model.